MRNA Trafficking in the Nervous System: A Key Mechanism of the Involvement of Activity-Regulated Cytoskeleton-Associated Protein (Arc) in Synaptic Plasticity. (24th September 2021) - Fila, Michal; Diaz, Laura; Szczepanska, Joanna; Pawlowska, Elzbieta; Blasiak, Janusz
Abstract : Synaptic activity mediates information storage and memory consolidation in the brain and requires a fast de novo synthesis of mRNAs in the nucleus and proteins in synapses. Intracellular localization of a protein can be achieved by mRNA trafficking and localized translation. Activity-regulated cytoskeleton-associated protein (Arc) is a master regulator of synaptic plasticity and plays an important role in controlling large signaling networks implicated in learning, memory consolidation, and behavior. Transcription of the Arc gene may be induced by a short behavioral event, resulting in synaptic activation. Arc mRNA is exported into the cytoplasm and can be trafficked into the dendrite of an activated synapse where it is docked and translated. The structure of Arc is similar to the viral GAG (group-specific antigen) protein, and phylogenic analysis suggests that Arc may originate from the family of Ty3/Gypsy retrotransposons. Therefore, Arc might evolve through "domestication" of retroviruses. Arc can form a capsid-like structure that encapsulates a retrovirus-like sentence in the 3 ′ -UTR (untranslated region) of Arc mRNA. Such complex can be loaded into extracellular vesicles and transported to other neurons or muscle cells carrying not only genetic information but also regulatory signals within neuronal networks. Therefore, Arc mRNA inter- and intramolecular trafficking is essential for the modulation of synaptic activity required for memory consolidation and cognitive functions. Recent studies with single-molecule imaging in live neurons confirmed and extended the role of Arc mRNA trafficking in synaptic plasticity.